Pengembangan Elektronik Module IPA untuk Meningkatkan Keterampilan Proses Sains Siswa - Siti Alisah; Sajidan Sajidan; Muzzazinah Muzzazinah (Universitas Sebelas Maret, 2025)
This study aims to assess the initial effectiveness of an electronic module focused on Environmental Conservation material in improving students' Science Process Skills (SPS). This e-module was created using the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model and has been validated by experts. A medium-scale trial was conducted with a one-group pretest-posttest design involving 25 students from the upper grades. Data related to SPS were collected using pretest and posttest test instruments, then analyzed using the N-gain analysis method to measure the progress experienced in each SPS indicator. The results of the N-gain analysis showed that this e-module was significantly able to improve students' SPS skills. High increases (N-gain ≥ 0.7) were seen in the indicators